THE INFLUENCE OF INPUT HARMONIC SIGNAL’S FREQUENCIES ON CONTROL SYSTEMS DYNAMICS - A. G. Stryzhniou (Informatika)
The paper presents findings of the influence analysis of input harmonic signal’s frequencies on control systems dynamics. Different control system structures with discrete-time controllers have been considered. The system is stable with the feedback controller and unstable with the controller in the forward path. Different discrete-time shaping units (low-pass filters, rate limiters) with matched parameters have been applied for sustained oscillation and spontaneous drift elimination. The influence of input signal’s frequencies goes down if control system includes shaping units. At the same time, when using low-pass filters or rate limiters emerging additional delays need to be considered. The recommendations for the practical use of the investigation results are presented.